Upacara Yadnya Kadasa Suku Tengger dalam Perspektif Komunikasi Budaya (Studi di Kecamatan Sukapura, Kabupaten Probolinggo) - Pangestu, Yusya Giri (Journal of Management, Education and Communication, 2024)
This research aims to examine the meaning and process of cultural communication in the implementation of the yadnya kasada ceremony carried out by the Tengger people in the Sukapura area, Probolinggo Regency. This ceremony is a sacred tradition that has been passed down from generation to generation and is an important part of the cultural identity of the Tengger Tribe. The research method uses qualitative research with a phenomenological approach. The results showed that the meaning of the yadnya kasada ceremony message communicated by the tengger tribe community by expressing gratitude to God Almighty in a series of rituals and the process of inheriting the meaning of the yadnya kadasa ceremony in the tengger tribe community. The values communicated by the people of the Tengger tribe at the yadnya kasada ceremony are divided into 3 namely social, cultural and religious values. These findings reinforce the importance of preserving traditions as a means of cultural communication that plays a role in strengthening the collective identity of indigenous peoples